A Textual Metafunction Analysis of Vocational High School Students’ Speech - Afrian Restu Utama; Rudy Kristyanto Prabowo; Lusiana Indra Sari; Aziz Kurniawan (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2026)
This study examines the realization of theme and thematic progression in speeches of vocational high school students at the Erlangga English Speech Contest 2021. A Systemic Functional Discourse Analysis method was applied by focusing merely on textual metafunction. The research data were collected by downloading a video on YouTube entitled ‘National Grand Final Erlangga English Speech Contest 2021 Vocational High School’. Then, the video was transcribed into written form. I only took four speeches in this study and labeled VHS 1, VHS 2, VHS 3, and VHS 4. The result showed that all themes are realized in the speeches. The textual theme becomes the dominant one. It indicates that the speakers can create a logical connection between the meanings in the text. In the case of thematic progression, all thematic progressions are realized. The zig-zag pattern becomes dominantly employed. This frequent occurrence indicates that the speakers can develop the idea from the previous rheme to become the following theme. However, some grammatical errors still become an issue.